2006
DOI: 10.1037/0003-066x.61.7.690
|View full text |Cite
|
Sign up to set email alerts
|

Mental balance and well-being: Building bridges between Buddhism and Western psychology.

Abstract: has focused primarily on the diagnosis and treatment of mental disease, and only recently has scientific attention turned to understanding and cultivating positive mental health (Seligman & Csikszentmihalyi, 2000). The Buddhist tradition, on the other hand, has concerned itself over the past 2,500 years with cultivating exceptional states of mental well-being as well as identifying and treating problems of the mind (Smith, 1991). Toward a DialogueAlthough the records of the Buddha's discourses and later commen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
344
1
24

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 464 publications
(385 citation statements)
references
References 71 publications
(60 reference statements)
16
344
1
24
Order By: Relevance
“…Indeed, the present findings suggest that mindful awareness fosters a more adaptive, relaxed, and objective manner of responding to emotional situations as opposed to habitual, automatic, and conditioned reaction patterns. This would be consistent with evidence that the practice of mindfulness is associated with increased well-being (Wallace and Shapiro, 2006), and that emotional stability is a significant predictor of happiness (Hills and Argyle, 2001).…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Indeed, the present findings suggest that mindful awareness fosters a more adaptive, relaxed, and objective manner of responding to emotional situations as opposed to habitual, automatic, and conditioned reaction patterns. This would be consistent with evidence that the practice of mindfulness is associated with increased well-being (Wallace and Shapiro, 2006), and that emotional stability is a significant predictor of happiness (Hills and Argyle, 2001).…”
Section: Discussionsupporting
confidence: 76%
“…From this perspective, mindfulness may constitute an emotion regulatory strategy that targets cognitive processes related to the acceptance, interpretation and evaluation of emotional responses rather than voluntary emotional inhibition or modulation. This interpretation is highly compatible with the notions taught in the practice of mindfulness, such as acknowledging thoughts and feelings and observing them as temporarily passing events of the mind (Wallace and Shapiro, 2006). As a result, emotions dissipate more rapidly and cognitive resources can become available to the next event arising in the present moment.…”
Section: Brain Patterns Related To Mindfulness In Experienced Meditatsupporting
confidence: 59%
See 1 more Smart Citation
“…Mindful people can better cope with difficult emotions and thoughts without becoming overwhelmed, as they tend to be more creative and are open to new perceptual categories (Langer & Moldoveanu, 2000;Wallace & Shapiro, 2006). Mindfulness may lead to less rumination and habitual worrying, leading to higher resilience (Shapiro et al, 2007;Verplanken & Fisher, 2014).…”
Section: Mindfulness Resilience and Stressmentioning
confidence: 99%
“…© 2013 The Authors. Stress and Health published by John Wiley & Sons Ltd. Mindfulness has been called the 'heart' of Buddhist meditation (Kabat-Zinn, 2003;Thera, 1962), an essential tool to help identify the inner causes of suffering, the possibility of freedom from suffering and the means to realize such freedom (Wallace & Shapiro, 2006). Over the past 30 years, mindfulness has received a great deal of research attention within educational, health and psychiatric settings, because of its demonstrated links to psychological and physical health benefits (Baer, 2003;Keng, Smoski, & Robins, 2011).…”
mentioning
confidence: 99%